The Dynamics of Self-Disclosure in Adolescents with Mental Health Problems through the Instagram Account Into the Light - Salsabila Raudatun; Ahmad Tamrin Sikumbang (Journal Analytica Islamica, 2025)
This study aims to describe the dynamics of self-disclosure carried out by adolescents facing mental health challenges through social media, with the Into the Light account serving as a contextual space that represents these practices. This research adopts a qualitative case study approach that allows for an in-depth exploration of participants' subjective experiences. The findings reveal that self-disclosure plays an important role in enabling adolescents to express their feelings and thoughts in a safe and anonymous environment on social media. Factors such as emotional needs, trust levels, past experiences, and perceptions of a safe digital space influence adolescents' decisions to engage in self-disclosure. Although the Into the Light account was not directly involved as a participatory object in this research, its presence provides context for understanding digital spaces that support openness. This study contributes to broadening the understanding of how social media, as a supportive and inclusive environment, can promote adolescent mental health.